Beyond legal minds : sex, social violence, systems, methods, possibilities - Brant, William Allen, (Value Inquiry Book Series, 2018)
In this book, William Brant uncovers social causes of violence, in search of reductive measures. Multiple legal systems are explored as reducers and implementers of violence and threats, especially criminal justice systems. War, propagandizing, power, corporate and governmental involvement in social domination, statehood, dangerous ideologies, and tribal sexual domination are explored in many cultures. Various levels and methods are given for observing, measuring and analyzing how people think and behave regarding the law, including examples of comedy. A theoretical chapter presents legal theory in relation to conceptions of possibility and misconceptions. These ideas are applied to judiciaries, which expose winning strategies for lawyers' desired verdicts. Dr. Brant accounts for the interconnections between sexual selection, legal systems and wars.